The Effect Of Brand Innovativeness And Social Media Marketing Activity On Brand Loyalty Mediated By Brand Love In Local Luxury Fashion Brands - Arie Andani Savitri; Fatchur Rohman; Sri Palupi Prabandari (Al-Makki Publisher, 2023)
This study examines the effect of brand innovativeness and social media marketing activity on brand loyalty and brand love, the effect of brand love on brand loyalty, and the effect of brand love mediating brand innovativeness and social media marketing activity. The research approach used in this research was a quantitative approach with explanatory research. The sampling technique used in this research is non-probability sampling with a purposive sampling technique with 250 respondents. The data collection technique used in this study was a questionnaire distributed online via Google Forms. The data measurement technique used in this study is a Likert Scale. Data analysis methods through Validity Test, Reliability Test, Descriptive Analysis, and Partial Least Square (PLS) based SEM Analysis. The results showed that 1) brand innovativeness was proven to affect brand loyalty to the Suedeson brand, 2) Brand innovativeness is proven to affect brand love for the Suedeson brand, 3) Social media marketing activity is proven to affect brand loyalty for the Suedeson brand, 4) Social media marketing activity is proven to affect brand love for the Suedeson brand, 5) Brand love is proven to affect brand loyalty for the Suedeson brand, 6) brand innovativeness is proven to affect brand loyalty through brand love mediation.